2011
DOI: 10.1111/j.1439-0388.2010.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of ‘breeding field test status’ in Icelandic horses

Abstract: Genetic evaluation of Icelandic horses is currently based on results from breeding field tests where riding ability and conformation of the horses are evaluated over the course of 1-2 days. Only a small part of registered horses attend these field tests, and it can be assumed that these are not a random sample of the population. In this study, the trait test status was introduced, describing whether a horse was assessed in a breeding field test. This trait was analysed to find out whether it has a genetic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…As a percentage of the mean, the same traits plus working equitation trials showed the highest responses, but in the best cases the annual genetic trend did not exceed 0.2% of the mean. The observed responses are in line with the genetic trends reported for conformation traits in Icelandic horses (Albertsdottir et al, 2011), and are somewhat better than those observed in Swedish Warmblood (Arnason, 1987). In our analyses of functional traits, only records collected after 2000 were considered in the analysis of dressage events, and the modest genetic trend achieved is, nevertheless, better than that observed in Selle Français (Dubois and Ricard, 2007), but lower than the results reported for the Swedish Warmblood (Viklund et al, 2011) and for a group of horse breeds competing in dressage events in Great Britain (Stewart et al, 2010).…”
Section: Tablesupporting
confidence: 70%
See 1 more Smart Citation
“…As a percentage of the mean, the same traits plus working equitation trials showed the highest responses, but in the best cases the annual genetic trend did not exceed 0.2% of the mean. The observed responses are in line with the genetic trends reported for conformation traits in Icelandic horses (Albertsdottir et al, 2011), and are somewhat better than those observed in Swedish Warmblood (Arnason, 1987). In our analyses of functional traits, only records collected after 2000 were considered in the analysis of dressage events, and the modest genetic trend achieved is, nevertheless, better than that observed in Selle Français (Dubois and Ricard, 2007), but lower than the results reported for the Swedish Warmblood (Viklund et al, 2011) and for a group of horse breeds competing in dressage events in Great Britain (Stewart et al, 2010).…”
Section: Tablesupporting
confidence: 70%
“…A positive genetic trend has been achieved in different equestrian disciplines, including dressage, show jumping, eventing and endurance (Ricard and Touvais, 2007;Thoren Hellsten et al, 2009;Viklund et al, 2011), but also in conformation aspects (Albertsdottir et al, 2011;Fioretti et al, 2005;Miglior et al, 1998). For racing performance, however, the results have been less consistent, because even though a positive genetic trend for speed has been reported for several breeds (Gaffney and Cunningham, 1988;Klemetsdal, 1992;Mota et al, 2005;Oki and Sasaki, 1996;Olsen et al, 2011;Willham and Wilson, 1991), no reduction in winning times has been observed for the major horse races over the last 50 years (Gardner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A direct comparison with our results is not possible, because the studied traits have not the same meaning and scoring procedures, but it is interesting to notice that in the Icelandic Horse the estimated heritability for general impression was 0.63 (Albertsdóttir et al, 2011) while for the Pura Raza Español the estimate was 0.08 (Sánchez et al, 2013). Our estimated heritability for harmony was 0.18, which is in the lower range of the values found in the literature and in line with the estimate of 0.14 reported for overall impression in Lusitano horses (Vicente et al, 2014a).…”
Section: Heritability and Repeatability Estimatesmentioning
confidence: 91%
“…There are three basic approaches to performance evaluation: station tests, field tests and competition. Also a variety of weighting proportions in the total score for traits has been observed (Albertsdottir et al, 2011). More and more efforts have been undertaken, however, towards genetic connectedness between country-members of Interstallion (Ruhlmann et al, 2009).…”
Section: Resultsmentioning
confidence: 99%